Chromosomal aberrations +1q21 and del(17p13) predict survival in patients with recurrent multiple myeloma treated with lenalidomide and dexamethasone - Klein, Ulrike; Jauch, Anna; Hielscher, Thomas; Hillengaß, Jens; Raab, Marc-Steffen; Seckinger, Anja; Hose, Dirk; Ho, Anthony Dick; Goldschmidt, Hartmut; Neben, Kai (Cancer, 2011)
Background: In the era of novel agents such as lenalidomide and bortezomib, risk stratification by chromosomal abnormalities may enable a more rational selection of therapeutic approaches in patients with multiple myeloma (MM). Methods: The authors analyzed the prognostic value of deletion del(13q14), del(17p13), +1q21, translocation t(4;14), t(11;14), and t(14;16) by fluorescence in situ hybridization (FISH) in a series of 92 patients with recurrent MM who were treated with lenalidomide and dexamethasone (len/dex) at the study center. Results: Patients carrying del(13q14) or t(14;16) were found to have a shorter median time to disease progression (TTP) of 5.1 months (vs 14.4 months; P = .009) and 2.0 months (vs 10.5 months; P <.001), respectively. However, no effect on TTP was observed in patients harboring del(13q14) as an exclusive chromosomal aberration without the concomitant presence of t(4;14) or del(17p13). The median overall survival (OS) for patients with del(17p13) or +1q21 was 6.7 months (P = .002) and 8.3 months (P < .001), respectively, whereas the median OS for patients carrying none of these abnormalities was not reached. Multivariate analysis revealed that the effects of del(17p13) and +1q21 on OS were independent of patient age as well as the type and number of regimens administered before len/dex. Conclusions: The results of the current study suggest that the prognostic significance of t(4;14) may be ameliorated or eliminated in patients treated with len/dex, whereas the presence of del(17p13) or +1q21 is still associated with a dismal OS. The presence of t(11;14) and del(13q14) as exclusive chromosomal aberrations indicates no impact on outcome. Because of its rarity in MM, a confirmation of the prognostic role of the t(14;16) aberration is still pending.
Published online December 3, 2010
Gesehen am 18.08.2022